Development of Nano-Silver Functionalized Wound Dressings Using Wrightia tinctoria Extract for Enhanced Antibacterial Activity Against MRSA and Staphylococcus aureus - Shree, Muthu Karuppan Gayathri; Christie, Swamidurai Arul Diana; Kumar, Sundaram Raj (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Wound infections remain a major source of postoperative morbidity, accounting for about a quarter of the total number of nosocomial infections. This leads to errors in establishing the true incidence of their occurrence but undoubtedly decreases the overall real cost and length of hospital stay. The healing of defected skin tissue is a complex process, especially for chronic wounds. Poor healing of these wounds may cause extensive suffering and high cost for patients. Traditional wound dressings are typically designed for a single function and they cannot satisfy all requirements for the whole process of wound healing. So it is essential to develop new types of wound dressings with many functions for wound healing. In specific, adding an antibacterial function to the dressings has been shown to be of great benefit during healing of any kind of wounds. Nano‑silver is widely used in wound treatment as of various advantages, it has wide antibacterial spectrum and lower drug resistance. Therefore, wound dressings loaded with nano‑silver have attracted widespread attention in wound healing. In this work we focused on nano‑silver functionalized wound dressings including their preparation methods, antibacterial performances and classification of nano‑silver wound dressings. The toxicity of nano‑silver based wound dressings is discussed and the prospective research direction is elaborated. This work aims to provide a little guidance for the research of nano‑silver functionalized polysaccharide-based wound dressings. The study showed the ability to synthesize environmentally friendly silver nanoparticles (AgNPs) using extracts from Wrightia tinctoria.